Development of a severe mitral valve stenosis secondary to the treatment of mitral regurgitation with a single MitraClip - Oßwald, Anja; Jabbari, Odeaa Al; Saleh, Walid K. Abu; Barker, Colin; Ruhparwar, Arjang; Karmonik, Christof; Loebe, Matthias (Journal of cardiac surgery, 2016)
We report a patient with class III heart failure symptoms due to mitral regurgitation (MR) subsequent to nonischemic cardiomyopathy. The patient underwent percutaneous transcatheter mitral valve repair using a single MitraClip, which reduced the MR; however it created mild-to-moderate mitral stenosis, which progressed to severe mitral stenosis. Subsequently the patient underwent mitral valve replacement surgery. doi: 10.1111/jocs.12692 (J Card Surg 2016;31:153-155)
Gesehen am 13.10.2020